Random Numbers: Pseudo-Random and True Random Numbers - Nabiyev Fazliddin (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
This article provides an overview of random numbers, including their definition, types (pseudo-random and true random), advantages and disadvantages of each type, how they are generated, and their applications